Androgen treatment in adolescent males with hypogonadism - Rey, Rodolfo Alberto (2020)
During adolescence, androgens are responsible for the development of secondary sexual characteristics, pubertal growth, and the anabolic effects on bone and muscle mass. Testosterone is the most abundant testicular androgen, but some effects are mediated by its conversion to the more potent androgen dihydrotestosterone (DHT) or to estradiol. Androgen deficiency, requiring replacement therapy, may occur due to a primary testicular failure or secondary to a hypothalamic–pituitary disorder. A very frequent condition characterized by a late activation of the gonadal axis that may also need androgen treatment is constitutional delay of puberty. Of the several testosterone or DHT formulations commercially available, very few are employed, and none is marketed for its use in adolescents. The most frequently used androgen therapy is based on the intramuscular administration of testosterone enanthate or cypionate every 3 to 4 weeks, with initially low doses. These are progressively increased during several months or years, in order to mimic the physiology of puberty, until adult doses are attained. Scarce experience exists with oral or transdermal formulations. Preparations containing DHT, which are not widely available, are preferred in specific conditions. Oxandrolone, a non-aromatizable drug with higher anabolic than androgenic effects, has been used in adolescents with preserved testosterone production, like Klinefelter syndrome, with positive effects on cardiometabolic health and visual, motor, and psychosocial functions. The usual protocols applied for androgen therapy in boys and adolescents are discussed.